Employees’ improvisational behavior: Exploring the role of leader grit and humility - Rego, J.; Vitória, A.; Cunha, M. P.; Owens, B. P.; Ventura, A.; Leal, S.; Valverde, C.; Lourenço-Gil, R. (Human Performance, 2022)
In spite of a growing interest for improvisation in organizations, the microfoundations of improvisation have not been theorized yet. Exploring these microfoundations, we study how employees’ psychological capital (PsyCap) acts as a critical cluster of resources to face improvisational challenges and how leaders who convey grit (operationalized as perseverance of effort: Grit-PE), counterbalanced with humility, create conditions to develop those resources. By building upon the conservation of resources and the dual-systems model of self-regulation theories, our empirical studies suggest that the interaction between two leader-conveyed resources (Grit-PE and humility) creates a contextual resource that helps employees develop PsyCap, thus making them more likely to improvise. The positive effect of high Grit-PE in leaders on employees’ improvisation materializes mainly when leaders also are humble.